Parameters of physical development in highly skilled skiers aged 18-20 in the third year of the Olympic cycle - Golovachev, A.I.; Kolyhmatov, V.I.; Shirokova, S.V.; Grushin, A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to examine the characteristics of the development of physical qualities in highly skilled ski racers aged 18-20 in the third year of the Olympic training cycle. Methods and structure of the study. 11 athletes from the Russian junior cross-country skiing team aged 18-20, with qualifications ranging from candidate master of sports to master of sports, participated in comprehensive examinations conducted at the ROC and VNIIFK innovation center at the beginning and end of the preparatory period of the third year (2024-2025 season) of the Olympic cycle (OC). The examination program included an assessment of leading physical qualities and abilities. To this end, athletes were asked to undergo testing consisting of two methods that measure the reaction force of the support when performing jumping exercises at maximum power on a PD-2 tensodynamometric platform (VISTI, Russia), used to assess explosive leg strength (ELS) and measure mechanical power when performing work with the arms on a SkiErg Concept-2 ergometric machine (USA), used to assess explosive arm strength (EAS) and speed-strength endurance of the arms (SSEA) [1]. Test procedures, means and methods of monitoring the indicators under study were carried out on the basis of methodological recommendations developed to assess the development of the physical qualities of athletes of the Russian national teams and the immediate reserve. They were maintained throughout all stages of the Olympic cycle [2, 3]. Results and conclusions. The results of the comparative analysis show that a distinctive feature of the development of the leading physical qualities of cross-country skiers at the end of the preparatory period (PP) of the third year of the Olympic training cycle is the multi-level increase in the studied indicators, differentiated by the nature of muscle activity when demonstrating explosive arm strength (work per hand movement in terms of absolute and relative values: Aabs. +7.0% and Arel. +6.9%) and legs (in terms of force gradient: Jabs. and Jrel. +8.2%) in relation to the speed-strength endurance of the arms (in terms of power output in the 5-minute 5PMR test: Nabs. +11.8% and Nrel. +11.7%). At the same time, the greatest decrease in the degree of deviation from the model level of the 2022 Olympian, primarily (in terms of the physical qualities studied), occurs in the explosive strength of the arms (Aabs. -5.1% and Arel. -2.8%), reaching the lower limit of model level, and explosive leg strength (by force gradient: Jab. -10.0% and Jrel. -7.9%), approaching the lower limit of model level, and the continuing lag in the level of speed-strength endurance of the arms (Nabs. -11.3% and Nrel. -9.2%). The greatest differences in relation to model level in terms of the physical qualities studied remain in terms of absolute values, reflecting their dependence on total body size.